Rotação Faraday de Éxciton-Polariton em uma microcavidade - Danielle Cristina Teles Ferreira (2016)
The optics microcavity attract the attention of the scientic community for due to their large potential for applications in optoelectronic new generation devices. It is possible to insert a gain medium on it, as a simple quantum well, which creates an environment for the formation of exciton polaritons when the exciton interacts with the conned electromagnetic eld. The excitons polaritons, or simply polaritons, areone of the most impressive quasipaticles made of light and matter. This work will show experimental evidence of Faraday rotation without the application of external magnetic eld in microcavities. In order to achieve this goal, the photoluminescence technique will be employed along with an analysis of the light polarization emitted by a semiconductor microcavity with polaritons formation.